Implikasi Hukum Terhadap Notaris (Suami-Istri) Yang Membuka Kantor Bersama Dalam Bentuk Persekutuan Perdata - Leo Pernando (Faculty of Law Universitas Islam Indonesia, 2022)
Article 20 of Law Number 2 of 2014 on Amendments to Law Number 30 of 2004 on the Notary Public states that a Notary can carry out their position in the form of a civil partnership while still paying attention to independence and impartiality in carrying out his position. The formulation of the problem formulated in this research is, first, what are the legal implications for notaries for married couples opening a joint office in the form of a civil partnership? and secondly, what form of independence and secrecy does a notary who is bound by marriage carry out in carrying out his position? The type of research used is juridical-normative research with a statutory approach. The results of this study indicate that the first is the separation of joint assets between husband and wife and the obligation to provide income in the joint office. The two forms of independence and secrecy carried out by a notary who is bound by marriage, that the notary acts in a trustful, honest, thorough, independent, impartial manner, safeguards the interests of the parties involved in legal actions and keeps everything confidential about the Deed he made and all information obtained for making The deed is in accordance with the oath of office, in order for the notaries who are members of the joint office carry out the position of a notary in the same way as the implementation of the position of a notary in general.Key Word: Implications, Notary Joint Office, Civil Partnership AbstrakPasal 20 Undang-Undang Nomor 2 Tahun 2014 tentang Perubahan Undang-Undang Nomor 30 Tahun 2004 tentang Jabatan Notaris menyebutkan bahwa notaris dapat menjalankan jabatannya dalam bentuk persekutuan perdata dengan tetap memperhatikan kemandirian dan ketidakberpihakan dalam menjalankan jabatannya. Rumusan masalah yang dirumuskan dalam penelitian ini pertama apa implikasi hukum terhadap notaris pasangan suami istri membuka kantor bersama dalam bentuk persekutuan perdata? dan kedua bagaimana bentuk kemandirian dan kerahasiaan yang dijalankan notaris yang terikat dalam perkawinan dalam menjalankan jabatannya? Jenis penelitian yang digunakan adalah penelitian yuridis-normatif dengan pendekatan perundang-undangan. Hasil penelitian ini menunjukkan bahwa pertama terjadinya pemisahan harta bersama antara suami istri dan kewajiban untuk memberikan pemasukan dalam kantor bersama. Kedua bentuk kemandirian dan kerahasiaan yang dijalankan oleh notaris yang terikat perkawinan, bahwa notaris bertindak amanah, jujur, saksama, mandiri, tidak berpihak, menjaga kepentingan pihak yang terkait dalam perbuatan hukum dan merahasiakan segala sesuatu mengenai Akta yang dibuatnya dan segala keterangan yang diperoleh guna pembuatan Akta sesuai dengan sumpah jabatan, sehingga notaris yang tergabung dalam kantor bersama menjalankan jabatan notaris dilakukan sama seperti pelaksanaan jabatan notaris pada umumnya.Kata-Kata Kunci: Implikasi, Kantor Bersama Notaris, Persekutuan Perdata